Polityka Unii Europejskiej w zakresie badań, rozwoju technologicznego i innowacji - szansa dla Polski - Słupińska, Monika (EU Policy Regarding Research, Technological Development and Innovation - Opportunities for Poland, 2005)
The evolution of EU RTD policies shows the changing position of EU competitiveness in the world market as well as indicates the deepening of European integration process itself. European Union's actions in the field of research and development serve as the supplementary instruments for reinforcement and coordination of national policies. Such a common policy is strictly dependent on political decisions whose main goal is to improve EU position in the world. The latest conclusions of European Council Summits prove the definite will of the EU countries to undertake concrete actions focused on building knowledge- based European economy and giving to the EU the position of the most competitive economy in the world.Even if the previous and current European RTD policy instruments have been subject to several critical opinions, for the Polish sector of science and technology development active participation in EU programmes can be a way to create a national and regional innovation systems and start a process of emerging of learning regions able to fulfill European standards.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 99-106